Para além de uma concepção estática de constitucionalismo: soberania e as engrenagens constitucionais em movimento - Carlos Alberto Esteves (2018)
This work arises from the perception that, although the Latin America contemporary constitutionalism is referred to as a "new" constitutional phenomenon in relation to the hegemonic constitutionalism of liberal matrix, studies on the subject do not systematically explore what are the structuring characteristics of this parameter. Therefore, the objective of this dissertation is to propose an alternative conception of constitutionalism that is in line with the demands of a deepening democracy, starting from the identification of the fundamental elements that particularize the hegemonic liberal constitutional tradition. From a theoreticalnormative profile, the approach is based on the identification of the elements that give form to the constitutionalism inaugurated in the eighteenth century and then the constitutionalism of the twentieth century, as well as the relationship formats that are established with democracy. Finally, having the common structuring component of both cycles as the parameter, I propose a possible new format of constitutionalism which may represent a step forward in relation to the hegemonic liberal paradigm.